On the possibility of state regulation in the extensive path of development of production - Bahaliubskaya-Siniakova, Katsiaryna S.; Kalitine, Boris S. (Journal of the Belarusian State University. Economics, 2019)
The paper explores the possibilities of state regulation of the volume of the entrepreneur’s output in expanded production. It is assumed that the state applies preferential tax rates as the main incentives. The mathematical model of the company’s proceeds is the foundation of the study. Based on the results of the model study, the conditions for maximizing the entrepreneur’s income are revealed: the enterprise achieves maximum benefits in the conditions of increasing production in cases of the minimum preferential tax rate, the maximum values of the rate of price growth and the coefficient of costs in the production of an additional unit of products. The research also found that the maximization of income arises when the enterprise operates in the markets of goods with high price elasticity or in the markets of goodswith price elasticity close to zero.
Keywords: state regulation; income; preferential terms; tax rate; build-up of output